Analisis Pengembangan Ekowisata Mangrove secara Syariah ditinjau dari Sosial Dan Ekonomi Masyarakat - Nagara, Patria; Wahyu, Sartika Dewi Hendra; Ikhfariza, Rahmini (El-kahfi | Jurnal Ekonomi Islam, 2023)
The purpose of this study was to obtain an in-depth description and understanding of the impact of mangrove forest ecotourism development on the social and economic community in Apar Village, Pariaman City. This study uses a qualitative approach with in-depth interview data collection techniques and supports in the form of documentation and observation using purposive sampling technique. This research was carried out in Simpang Apar Village, Pariaman City, from March to November 2022. The results of the research on the development of mangrove forest ecotourism on the social and economic aspects of the community in the Apar Village, Pariaman City are that the development and management of mangrove forests has experienced significant changes from year to year and has undergone good management, while the impact of mangrove forest ecotourism on the socio-economic community which is considered the most influential in this ecotourism activity is the environmental carrying capacity, other impacts are opening up new jobs, increasing the amount of income, increasing community welfare.